2004
DOI: 10.1039/b406569g
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation potentials and electron donation to photosystem II of manganese complexes containing bicarbonate and carboxylate ligands

Abstract: The oxidation potentials of Mn II in aqueous solutions of bicarbonate, formate, acetate and oxalate are reported as a function of concentration and compared to the rate of photooxidation of these solutions by the Mn-depleted water-oxidizing complex of photosystem II (apo-WOC-PSII) from peas. Although all the carboxylate species lower considerably the oxidation potential of Mn II , only bicarbonate stimulates the electron transfer from Mn II to apo-WOC-PSII. On the basis of the electrochemical data it is propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 33 publications
(63 reference statements)
5
29
0
Order By: Relevance
“…Interestingly, O 2 evolution measurements indicate that the presence of bicarbonate anion enhances the rate of photoassembly [80]. This effect can be rationalized as carboxylate coordination of the Mn(H) ion is known to stabilize the corresponding Mn(II) → Mn(III) oxidation potential from 1.5 to 0.5 V when bound to PSII [81]. Conveniently, this new potential is well within the range of 1.1 V accessible by the photooxidized active-site tyrosyl radical ( ).…”
Section: Past Studiesmentioning
confidence: 99%
“…Interestingly, O 2 evolution measurements indicate that the presence of bicarbonate anion enhances the rate of photoassembly [80]. This effect can be rationalized as carboxylate coordination of the Mn(H) ion is known to stabilize the corresponding Mn(II) → Mn(III) oxidation potential from 1.5 to 0.5 V when bound to PSII [81]. Conveniently, this new potential is well within the range of 1.1 V accessible by the photooxidized active-site tyrosyl radical ( ).…”
Section: Past Studiesmentioning
confidence: 99%
“…However, no experimental evidence characterizing these subsequent intermediates is yet available. 1 and IM 1 *-Bicarbonate coordination of free Mn 2+ in water lowers the oxidation potential for photoconversion to Mn 3+ by a large amount (0.5-0.6 V vs. NHE) [91]. This thermodynamic stabilization is thought to be responsible for the increased stability of the Mn 3+ photoactivation intermediate that forms in the presence of bicarbonate, as seen by slowing of the recombination reaction that causes its decay [49].…”
Section: Trapping Assembly Intermediatesmentioning
confidence: 99%
“…The oxidation potential of Mn-bicarbonate complex (0.52-0.67 V ) is close to the midpoint redox potential of the primary electron donor in the RCs of anoxygenic bacteria (Kozlov et al 2004) and therefore it has been suggested (Dismukes et al 2001) that the capability of bicarbonate to form easily oxidizable complexes with manganese ions might be critical to the evolutional origin of the first O 2 -evolving cyanobacteria from a non-oxygenic bacterial precursor in the Archean period (O2.2 Gyr ago) when the concentration of bicarbonate dissolved in water was 30-30 000 times greater than today.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in redox properties of manganese ions upon formation of complexes with bicarbonate evidently play a key role in the effect described above. In fact, upon the addition of NaHCO 3 to an aqueous solution of Mn 2C , the potential for oxidation of Mn 2C to Mn 3C was shifted from 1.18 to 0.52-0.68 V at pH 8.3 as a result of formation of bi(carbonate) complexes (Kozlov et al 1997(Kozlov et al , 2004Dasgupta et al 2006). Formation of Mn complex with carboxylates (formate, acetate) induced similar lowering of the oxidation potential; however, only bicarbonate stimulated the electron transfer from Mn 2C to PSII reaction centres (RCs; Kozlov et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation